Miniaturization of antenna using metamaterial loaded with CSRR for wireless applications - Pande, Suyog V.; Patil, Dipak P. (Institute of Advanced Engineering and Science, 2024)
This paper proposes a compact decagon antenna for wireless applications based on inspired metamaterial (MTM) loaded with a modified complementary split ring resonator (CSRR). A MTM loaded with CSRR is used to achieve a size reduction of 50% when compared to a traditional antenna. The suggested decagon antenna's ground plane has been loaded with CSRR. The antenna was made on an FR4 substrate with a thickness of 1.6 mm and εr=4.4 and has a very small dimension of 0.288 λ_0x0.272 λ_0x0.013 λ_0 (where λ_0 represent center frequency at 2.4 GHz). The given antenna has a 90 MHz bandwidth (2.40-2.50 GHz) with a peak gain of 2.36 dB. The presented design is validated by showing simulated results of the S parameter, VSWR, gain, surface current, and radiation pattern. The proposed antenna is well suited for wireless applications.